2012
DOI: 10.1371/journal.pone.0034238
|View full text |Cite
|
Sign up to set email alerts
|

Finding a Needle in the Virus Metagenome Haystack - Micro-Metagenome Analysis Captures a Snapshot of the Diversity of a Bacteriophage Armoire

Abstract: Viruses are ubiquitous in the oceans and critical components of marine microbial communities, regulating nutrient transfer to higher trophic levels or to the dissolved organic pool through lysis of host cells. Hydrothermal vent systems are oases of biological activity in the deep oceans, for which knowledge of biodiversity and its impact on global ocean biogeochemical cycling is still in its infancy. In order to gain biological insight into viral communities present in hydrothermal vent systems, we developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 108 publications
0
22
0
1
Order By: Relevance
“…Only 1% of the sequences were attributed to the presence of eukaryote (fungal-probably from spores) and viruses, which compares favorably to other reports. 157,160 In most studies DNA is isolated directly from the environment 159 or from microorganisms in aquatic 46,160 or soil environments. 161 No reports at all exist on the selective isolation of bacterial populations from wood.…”
Section: Resultsmentioning
confidence: 99%
“…Only 1% of the sequences were attributed to the presence of eukaryote (fungal-probably from spores) and viruses, which compares favorably to other reports. 157,160 In most studies DNA is isolated directly from the environment 159 or from microorganisms in aquatic 46,160 or soil environments. 161 No reports at all exist on the selective isolation of bacterial populations from wood.…”
Section: Resultsmentioning
confidence: 99%
“…(203–205) demonstrated evidence of a robust bacteriophage population in periodontally healthy subjects and reported that only about 7–22% of the streptococcal populations of saliva are stable over time. As is the case in other ecosystems in nature, viruses appear to be one of the main driving forces behind changes in the microbial populations (208, 214, 255, 256).…”
Section: Future Considerationsmentioning
confidence: 99%
“…The pre-filter samples were fixated in 96 % ethanol and stored at -80°C, while the rest of the filters were instantly placed in sterile 1.5 mL cryo-tubes and frozen in liquid nitrogen before storage at -80°C for further analysis. The water samples were further filtered using 0.22-lm Sterivex TM filters (Millipore TM , Merck KGaA Darmstadt, Germany) to extract prokaryote DNA (unpublished data), and finally, viruses were analysed and described in Ray et al (2012).…”
Section: Field Samplingmentioning
confidence: 99%